Temperature-Dependent Dynamic Strain Aging in Selective Laser Melted 316L - Diepold, Benedikt; Neumeier, Steffen; Meermeier, Annalena; Höppel, Heinz Werner; Sebald, Torsten; Göken, Mathias (Advanced Engineering Materials, 2021)
Additively manufactured austenitic stainless steel AISI 316L (EN 1.4404, X2CrNiMo17-12-2) is used at higher temperatures, e.g., in space applications. However, the high-temperature properties of such materials have not been analyzed in detail yet. Thus, selective laser melted (SLM) 316L is tested in the solution-annealed condition by compression and tensile tests at temperatures between 25 and 877 °C. The compressive strength of SLM 316L is higher in comparison with the conventionally produced reference material due to hardening by a high dislocation density and a fine substructure. However, tensile tests reveal a loss in ductility of the SLM material at temperatures between 300 and 627 °C, where the elongation to fracture is reduced from 65% to 39%. Alloying elements cause serrated yielding in the affected temperature range. Together with an increased normalized work-hardening rate and a negative strain rate sensitivity, dynamic strain aging is found to cause the reduction of ductility.
CRIS-Team Scopus Importer:2021-07-02
Keywords: dynamic strain aging; laser beam melting; microstructures; Portevin–Le Chatelier effect; serrations; strain rate sensitivity; strengths